Experimental and Numerical Studies on Post-Fracture Behavior of Simply Supported Composite Twin I-Girder Bridges. Issue 2 (3rd April 2019) - Lam, Heang; Lin, Weiwei; Yoda, Teruhiko
ABSTRACT: This study was carried out to investigate the post-fracture behavior of the composite twin I-girder bridge systems. One intact specimen and one damage specimen with fracture at mid-span section were tested under static load test. By comparing the pre- and post-fracture behavior, significant reduction of system stiffness and load carrying capacity are observed. Nevertheless, composite twin I-girder bridge system will not collapse under dead load and be able to carry sufficient live load which qualifies the bridge as a redundant system in fracture condition. Meanwhile, by using finite element method with nonlinear analyses, fracture at different sections are analyzed. Results proved that the fracture of whole web and bottom flange at mid-span section is the most fracture critical location comparing to fracture at other locations. In addition, by comparing the performance of one girder and twin-girder models, the adjacent girder can be concluded as an essential component that ensures the safety of the composite twin I-girder bridge system in fracture condition.